Magnetic responsive cell-based platforms for tissue engineering applications - Santos, Lúcia Isabel Ferreira (2023)
The major goal of tissue engineering consists on the development of biological substitutes to repair or replace damaged tissues. However, the fabrication of clinically relevant tissue replacements is still illusory, hampering their transactional to clinical practices. During the design of tissues in vitro, all the functional and morphological features must be recapitulated. To address this challenge, scaffold-free approaches have emerged as powerful strategies for the fabrication of tissue constructs with enhanced deposition of extracellular matrix, essential for the natural development of the tissue architecture. Nevertheless, the traditional approaches still fail on engineering tissues with high level of complexity, as seen in stratified and hierarchical conformations, as well with adequate mechanical performance. Therefore, this PhD proposal aimed to develop improved tissue substitutes that closely mimic key functional aspects of the native microenvironment. By using magnetized cells as basic living units, we propose the fabrication of magnetic membranes of cells through magnetic force-based tissue engineering (Mag-TE). The magnetic character of the created tissues allowed a precise control over cells’ positioning and, consequently, an extremely guided-assembling of the tissues. Following this strategy, cohesive and robust macrotissues with enhanced mechanical behavior were fabricated, circumventing one of the major limitations of scaffold-free approaches which includes the development of mechanically weak tissue constructs. Concerning the architecture of the native tissues, magnetic living substitutes with intricate geometries were developed, attesting the versatility of this approach. Another problematic regarding the development of tissue substitutes is the lack of adequate diffusion of nutrients and oxygen, which may lead to premature cell death. To overcome this obstacle, we engineered pre-vascularized multilayered cell sheets, exhibiting preserved human vascular structures and the ability to integrate the host vasculature. In this thesis, small tissue units at the microscale were also designed through the combination of Mag-TE and a high-throughput platform. These microtissues could further act as living building blocks for the fabrication of larger heterotypic tissue constructs or as in vitro platforms for disease modelling and drug screening. Finally, by exploring the magnetic character of our improved living tissues, we evaluated the role of magnetic field on modulating the cell fate of tissues produced in vitro. Upon magnetic stimulation, we triggered the osteogenic differentiation of the magnetized tissues, opening new possibilities for advanced strategies in bone regeneration. Using an in vivo mice model, we were also able to stimulate tissue integration and the osteogenic differentiation of the implant in situ. By using magnetized cells as building materials, we envisaged the fabrication of complex multiscale and multifunctional tissues with clinical relevance. The magnetic features of the designed tissues could accelerate the translation of Mag-TE to the clinical practices, allowing the remote and in situ guiding of implants into the expected tissue function, while guarantying a feasible monitoring and tracking along the time.